STUDENTS' DIFFICULTIES IN ACADEMIC WRITING: A CASE STUDY IN HIGHER EDUCATION - Dinda Yarshal; Nurmairina Nurmairina; Ali Salim Ali Razaq (Sensei International Journal of Education and Linguistic, 2025)
Academic writing is very important for the students in higher education, but many students still find it difficult especially when they must write in English. This study discusses the difficulties of the students in academic writing. The study used a qualitative case study method. The data were collected from the essays of the students, interviews, and also documents. The result shows that the students have difficulties in grammar, vocabulary, and also in arranging the argument and using the references. Besides that, the students also feel that the feedback from the lecturer is not enough. Therefore the lecturers should teach academic writing more explicitly and give more feedback to the students.